Finding potential inhibitors from phytochemicals against nucleoprotein of crimean congo fever virus using in silico approach - Muhammad Ramzan; Sajid Mahmood; Adnan Amjad; Mohsin Javed; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Muhammad Saad; Namrah Zaka; Shazia Khurshid; Nasser S. Awwad; Hala A. Ibrahium; et al. (Scientific Reports)
Abstract The Crimean Congo virus has been reported to be a part of the spherical RNA-enveloped viruses from the Bunyaviridae family. Crimean Congo fever (CCHF) is a fatal disease with having fatality rate of up to 40%. It is declared endemic by the World Health Organization. Many outbreaks of CCHF have been reported over the years. Former studies on CCHF have reported that the nucleoprotein of CCHF, being a pivotal protein in the replication process of the virus, is a potential target for antiviral drugs. However, there is no specific drug that can be used to treat this fatal disease and laboratory testing is prohibited due to its pathogen level 4. This study aims to find a possible potential inhibitor of the nucleoprotein of CCHFV using modern techniques leading ultimately to the development of effective and natural drugs. In this study, a virtual screening procedure involving a docking process followed by the Molecular Dynamics method is used to find out the potential inhibitors of the nucleoprotein of CCHFV. Phytochemicals having pharmacological properties and approved by the Food and Drug Administration are docked over the nucleoprotein of CCHFV. The study signifies the use of Withanolide E as a drug for the treatment of CCHFV as the study depicts the potential of Withanolide E to inhibit the nucleoprotein of CCHFV using reliable and modern techniques.